Measurement of the Promoting Effect of Complex Conditions on the Adhesion Development in Curing Process of Cold Recycling Mixture with Emulsified Asphalt - Xueying Zhao; Baofu Ma (Advances in Civil Engineering)
The curing process of cold recycling mixture with emulsified asphalt is a process of emulsion breaking, water evaporation, and cement hydration, resulting in adhesion development and strength formation. There are many factors that affect this process, including curing temperature, curing time, reclaimed asphalt pavement (RAP) contents, and cement contents. However, the evaluation of the promoting effect of each factor is still not quite clear. Hence, in this paper, the curing temperature, curing time, and RAP contents were discussed to find out the dominating factor in this process. The development of moisture loss and indirect tensile strength (ITS) was measured and analyzed through establishing prediction models between them and curing time. Besides, the functional relationship between moisture loss and ITS was also analyzed to evaluate the promoting effect of each factor. The results showed that the curing temperature has a certain impact on the development of moisture loss and ITS and an increase in curing temperature would accelerate the reaction rate, while RAP contents can hardly affect this process. Through functional relationship between moisture loss and ITS, it was found that the development of early strength and adhesion was dominated by ITS despite the increase of curing temperature and RAP contents. Expanding the hydration effect of cement could promote the curing process. However, this dominating role weakened at higher temperature and moisture loss should be treated more carefully.